Prenatal Sonographic Features of Fetuses in Trisomy 13 Pregnancies (I) - Chih-Ping Chen (Elsevier, 2009)
Prenatal ultrasound is a powerful tool for detecting structural abnormalities in fetuses in trisomy 13 pregnancies. This article provides a comprehensive review of the prenatal sonographic features of trisomy 13, including the major structural abnormalities observed during the first trimester (omphalocele, holoprosencephaly, megacystis and congenital heart defects), the frequencies of second- and third-trimester sonographic features reported in previous studies, and the subtle sonographic findings observed during the second trimester (echogenic intra- cardiac foci, echogenic bowel, single umbilical artery, choroid plexus cysts and intrauterine growth restriction).